CircRNA FAT1 Regulates Osteoblastic Differentiation of Periodontal Ligament Stem Cells via miR-4781-3p/SMAD5 Pathway. (29th December 2021) - Ye, Yu; Ke, Yue; Liu, Liu; Xiao, Tong; Yu, Jinhua
Abstract : The ability of human periodontal ligament stem cells (PDLSCs) to differentiate into osteoblasts is significant in periodontal regeneration tissue engineering. In this study, we explored the role and mechanism of circRNA FAT1 (circFAT1) in the osteogenic differentiation of human PDLSCs. The proliferation capacity of PDLSCs was evaluated by EdU and CCK-8 assay. The abilities of circFAT1 and miR-4781-3p in regulating PDLSC differentiation were analyzed by western blot, reverse transcription-polymerase chain reaction (RT-PCR), alkaline phosphatase (ALP), and Alizarin red staining (ARS). A nucleocytoplasmic separation experiment was utilized for circFAT1 localization. A dual-luciferase reporter assay confirmed the binding relationship between miR-4781-3p and circFAT1. It was showed that circFAT1 does not affect the proliferation of PDLSCs. The osteogenic differentiation of PDLSCs was benefited from circFAT1, which serves as a miRNA sponge for miR-4781-3p targeting SMAD5. Both knockdown of circFAT1 and overexpression of miR-4781-3p suppressed the osteogenic differentiation of PDLSCs. Thus, circFAT1 might be considered as a potential target of PDLSCs mediated periodontal bone regeneration.